The Relation between Accounting Quality and Trade Credit - Naser Izadi Nia; Masoud Taheri (پژوهش‌های تجربی حسابداری, 2016)
Trade credit is one of the most important resources for short term financing. Several different factors affect trade credit one of the most important of which is accounting quality. Therefore, this paper examines the relation between a firm’s amount of trade credit and its accounting quality. Earnings smoothness, conservatism and earnings management are independent variables being used to proxy for accounting quality, and the dependent variable is trade credit. Earning to operating cash flow ration and discretionary accruals are criteria for earning smoothness and earning management respectively. Discretionary accruals are adjusted by Jones model (1995) and conservatism is calculated by Khan& Watts model (2009). Also, trade credit is calculated using payable accruals to total assets ratio. The sample consists of 127 firms listed in Tehran stock exchange from 2008 to 2013. The ordinary least square method is used to test hypotheses. Results show that there is no significant relation between amount of trade credit and earnings smoothness as well as conservatism while there is a significant negative relation between the amount of trade credit and earnings management. In other words, increasing in earnings management decreases trade credit.